Assessment of Refuse Dumpsite Impact on Groundwater Quality: A Case Study from Awotan, Ibadan, Oyo State, Nigeria - Ibrahim Adetayo Lawal; Chibueze Godwin Achi; Akinwale Oladotun Coker (Science, Engineering and Technology)
Groundwater, an essential freshwater resource, is critical to life and supports various industries. Unrestrained urban expansion and inefficient waste management practices endanger groundwater quality. This research examines the groundwater quality and impacts of the Refuse Waste Dumpsite located at Awotan, Ibadan. Additionally, this study provides a framework for assessing dumpsite impacts on groundwater, which can be applied to similar urban contexts worldwide, contributing to global efforts to ensure safe water quality. Samples of residential Well water near the dumpsite were collected to determine their physical, chemical, and bacteriological characteristics. The physical and chemical parameters investigated include Temperature, pH, Electrical conductivity, Nitrate, and Chloride, which were determined using the standard analytical methods. In contrast, bacteriological parameters such as Total Coliform and E.Coli Count were determined. Trace metals such as Pb and Fe were also determined to ascertain the relationship between pollutant levels and distances from the dumpsite and to evaluate compliance with WHO and NSDWQ water quality standards. Regression analysis revealed a strong correlation (R = 0.999, R² = 0.998) between dumpsite distance and chemical water quality, but the results were not statistically significant (p = 0.066). Chemical parameters like alkalinity (p = 0.484) and nitrate (p = 0.338) showed no significant impact from distance. For bacteriological quality, the model was statistically significant (p = 0.009) with an R² of 0.994. Total coliform (p = 0.055) was nearly significant, indicating potential distance-related bacterial contamination.  The findings underscore the pressing need for sustainable waste management to safeguard groundwater resources.